10th International Chemical and Biological Engineering Conference – CHEMPOR 2008 – Integrating Life Sciences & Engineering Special Section - Ferreira, Eugénio C. (2010)
This issue contains a special section with selected papers presented at the 10th International Chemical and Biological Engineering Conference – CHEMPOR 2008, held in Braga, Portugal, from the 4th to the 6th of September 2008, www.deb.uminho.pt/chempor2008. The conference was jointly organized by the University of Minho, “Ordem dos Engenheiros”, and the IBB – Institute for Biotechnology and Bioengineering, with the support of “Sociedade Portuguesa de Química” and “Sociedade Portuguesa de Biotecnologia”.